Pembuatan set eksperimen gerak jatuh bebas berbasis mikrokontroler dengan tampilan PC (Making a set of free fall motion experiments based on microcontroller with a PC display) - Yohanna Dasriyani; - Hufri; - Yohandri (Department of Physics – Universitas Negeri Padang UNP, 2015)
Experiment of free fall motion is one of phenomena in physic. Parameters of free fall motion still measured by stopwatch and meter. The purpose of research is development of free fall motion experiment set based on microcontroller with personal computer display. This instrument have highest precision and accuration. Average of measured result is 9,821 ± 0,025 with average of precicion relatif is 98,3% and average accuration is 0,992